Levels of 129I in coastal Pacific Ocean waters from southern California, 2011–2020 and the legacy of Fukushima - A. J. Timothy Jull; Ching-Chih Chang; George S. Burr; Li Cheng; Joellen Russell; Mang Lin; Daniel R. Crocker; Mark Thiemens; Dana Biddulph; Marc W. Caffee; Tom Woodruff; Christopher Glynn; et al. (Frontiers in Marine Science, 2026)
The Fukushima Daiichi Nuclear Power Plant accident released radionuclides directly into the ocean as a result of the Great East Japan Earthquake on March 11, 2011. This material has been transported across the Pacific Ocean and detected in the northeastern Pacific. We began a surface ocean 129 I monitoring program a few months after this disaster in June 2011, with samples from Scripps Pier, La Jolla, California, USA, with the expectation that surface currents originating off the east coast of Japan could eventually carry radionuclides to the La Jolla site. We could not identify a significant distinct signal that can be traced to Fukushima from the record from 2011-2020. We have however recorded a systematic seasonal 129 I time series record that appears to be due to surface circulation variations along the California coast, or perhaps other unexplained effects. We have reported on some of these effects previously, where we summarized results up to 2018. Since then, we have analyzed additional samples obtained during our sampling program for 2018–2020 from Scripps and also report other results collected during 2015–2016 from Newport Beach, CA, which had not been reported. These results support and expand on the previously published dataset.

Environmental Heterogeneity Throughout the Clarion-Clipperton Zone and the Potential Representativity of the APEI Network - Travis W. Washburn; Daniel O. B. Jones; Chih-Lin Wei; Craig R. Smith (Frontiers in Marine Science, 2021)
Environmental variables such as food supply, nodule abundance, sediment characteristics, and water chemistry may influence abyssal seafloor communities and ecosystem functions at scales from meters to thousands of kilometers. Thus, knowledge of environmental variables is necessary to understand drivers of organismal distributions and community structure, and for selection of proxies for regional variations in community structure, biodiversity, and ecosystem functions. In October 2019, the Deep CCZ Biodiversity Synthesis Workshop was conducted to (i) compile recent seafloor ecosystem data from the Clarion-Clipperton Zone (CCZ), (ii) synthesize patterns of seafloor biodiversity, ecosystem functions, and potential environmental drivers across the CCZ, and (iii) assess the representativity of no-mining areas (Areas of Particular Environmental Interest, APEIs) for subregions and areas in the CCZ targeted for polymetallic nodule mining. Here we provide a compilation and summary of water column and seafloor environmental data throughout the CCZ used in the Synthesis Workshop and in many of the papers in this special volume. Bottom-water variables were relatively homogenous throughout the region while nodule abundance, sediment characteristics, seafloor topography, and particulate organic carbon flux varied across CCZ subregions and between some individual subregions and their corresponding APEIs. This suggests that additional APEIs may be needed to protect the full range of habitats and biodiversity within the CCZ.

Public Perceptions of Mangrove Forests Matter for Their Conservation - Farid Dahdouh-Guebas; Gordon N. Ajonina; A. Aldrie Amir; Dominic A. Andradi-Brown; Irfan Aziz; Thorsten Balke; Edward B. Barbier; Stefano Cannicci; Simon M. Cragg; Marília Cunha-Lignon; David J. Curnick; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2020)

Perspective: Something Old, Something New? Review of Wasting and Other Mortality in Asteroidea (Echinodermata) - Ian Hewson; Brooke Sullivan; Elliot W. Jackson; Qiang Xu; Hao Long; Chenggang Lin; Eva Marie Quijano Cardé; Justin Seymour; Nachshon Siboni; Matthew R. L. Jones; Mary A. Sewell (Frontiers in Marine Science, 2019)